Klasifikasi dan Autentifikasi Tanaman Seurapoh (Chromolaena odorata Linn) Menggunakan Metode Kombinasi Spektroskopi Inframerah dan Kemometrik: Classification and Authentication of Seurapoh Plant (Chromolaena odorata Linn) Using a Combination of Infrared Spectroscopy and Chemometric Methods - Karma, Taufiq Karma; Kala, Pasyamei Rembune; Shofi, Shofi; Zafirah, Zafirah (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
This study classifies the Seurapoh plant (Chromolaena odorata Linn) collected from various locations across Aceh Province. The analysis aims to determine the influence of geographic differences on the origin of Seurapoh plants by performing classification and authentication. Seurapoh leaf samples in this study were obtained from several locations, including Aceh Besar, Sabang, Southwest Aceh, South Aceh, Aceh Jaya, Bireun, Bener Meriah, and Central Aceh. Classification of Seurapoh leaf extracts was carried out using Principal Component Analysis (PCA), while authentication was conducted using Linear Discriminant Analysis (LDA). The PCA score plot analysis results indicate that it can explain a total data variance of 62%. Based on the PCA score plot, samples generally form three distinct groups: Group 1 consists of samples from the highland region of Gayo, specifically Central Aceh (TA) and Bener Meriah (BM); Group 2 consists of samples from the coastal areas of Aceh, namely Southwest Aceh (ABD), South Aceh (AS), Aceh Jaya (AJ), and Bireun (Br); and Group 3 comprises samples from geothermal manifestation areas of Seulawah Agam and Jaboi. The classifications derived from PCA analysis were subsequently authenticated using LDA. The LDA analysis results indicate that the LDA model, based on cross-validation, accurately predicts the origin locations of Seurapoh leaf samples with a 100% accuracy rate.